2022
DOI: 10.1097/pcc.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

2022 Society of Critical Care Medicine Clinical Practice Guidelines on Prevention and Management of Pain, Agitation, Neuromuscular Blockade, and Delirium in Critically Ill Pediatric Patients With Consideration of the ICU Environment and Early Mobility

Abstract: RATIONALE:A guideline that both evaluates current practice and provides recommendations to address sedation, pain, and delirium management with regard for neuromuscular blockade and withdrawal is not currently available. OBJECTIVE:To develop comprehensive clinical practice guidelines for critically ill infants and children, with specific attention to seven domains of care including pain, sedation/agitation, iatrogenic withdrawal, neuromuscular blockade, delirium, PICU environment, and early mobility. DESIGN:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
236
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(253 citation statements)
references
References 348 publications
(551 reference statements)
4
236
0
13
Order By: Relevance
“…Previous studies reported that benzodiazepines are independent risk factors for delirium [ 16 , 17 ]; therefore, the replacement of benzodiazepines in favour for alternative drugs like alpha-2 agonists has been advocated [ 18 ]. The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative. It has been shown that alpha 2 -agonists is a safe and benzodiazepine sparing alternative for sedation in the pediatric population [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that benzodiazepines are independent risk factors for delirium [ 16 , 17 ]; therefore, the replacement of benzodiazepines in favour for alternative drugs like alpha-2 agonists has been advocated [ 18 ]. The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative. It has been shown that alpha 2 -agonists is a safe and benzodiazepine sparing alternative for sedation in the pediatric population [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few international and national clinical practice guidelines for the management of pain and sedation in children are available [ 5 – 8 ]. Except for the recently published PANDEM guideline, these guidelines were published more than 10 years ago with recommendations based on limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Protocols therefore should call for the sparing use of benzodiazepines in critically ill children, using opiates and alpha-2-agonist clonidine for firstline treatment ( 25 , 33 ). Even with our knowledge of side effects and negative long-term effects, there are still patients who are sedated using benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%
“…Disoprivan, for instance, is recommended for use in children for up to 48 h within the United States but its use is not allowed for long-term sedation in Europe because of risk for propofol infusion syndrome in children under the age of 16 ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation